Electrophoretic Determination of Symmetric and Asymmetric Dimethylarginine in Human Blood Plasma with Whole Capillary Sample Injection - Tůma, Petr; Sommerová, Blanka; Koval, Dušan; Couderc, François (International journal of molecular sciences, 2021)
Asymmetric and symmetric dimethylarginines are toxic non-coded amino acids. They are formed by post-translational modifications and play multifunctional roles in some human diseases. Their determination in human blood plasma is performed using capillary electrophoresis with contactless conductivity detection. The separations are performed in a capillary covered with covalently bonded PAMAPTAC polymer, which generates anionic electroosmotic flow and the separation takes place in the counter-current regime. The background electrolyte is a 750 mM aqueous solution of acetic acid with pH 2.45. The plasma samples for analysis are treated by the addition of acetonitrile and injected into the capillary in a large volume, reaching 94.5% of the total volume of the capillary, and subsequently subjected to electrophoretic stacking. The attained LODs are 16 nm for ADMA and 22 nM for SDMA. The electrophoretic resolution of both isomers has a value of 5.3. The developed method is sufficiently sensitive for the determination of plasmatic levels of ADMA and SDMA. The determination does not require derivatization and the individual steps in the electrophoretic stacking are fully automated. The determined plasmatic levels for healthy individuals vary in the range 0.36-0.62 µM for ADMA and 0.32-0.70 µM for SDMA.
Keywords: Limit of Detection; stacking; dimethylarginines; limita detekce; Humans; elektrická vodivost; Electrophoresis, Capillary; lidé; capillary coating; contactless conductivity detection; elektroforéza kapilární; Arginine; sample treatment; clinical analysis; Electric Conductivity; anionty; amino acid; arginin; acetonitrily; capillary electrophoresis; Acetonitriles; Anions